Biosimilars: what the oncologist should know. (22nd February 2019) - Thill, Marc; Thatcher, Nicholas; Hanes, Vladimir; Lyman, Gary H
As originator biologic medicines lose patent protection, some biopharmaceutical companies are focusing on developing similar versions of these costly and complex therapies with a goal of providing more affordable treatment options. Many of these molecules, known as biosimilars, are now approved worldwide and several more are expected to be introduced in the near future. As more biosimilars become available, it is important for clinicians to become familiar with this new category of products and understand how biosimilars are developed, how their development differs from that of originator biologics and how they differ from generics. This review aims to provide the practicing clinician with the knowledge needed to understand biosimilars, along with some guidance on their use in treating oncologic diseases.